Revue d'histoire nobiliaire et d'archéologie héraldique - Sandret, L. (Louis), 1815- (Paris, La Société bibliographique, 1882)
Includes section "Bibliographie nobiliaire."
No more published?
Mode of access: Internet.
Keywords: Nobility; Genealogy; Nobility -- France -- Periodicals; Genealogy -- Periodicals; France; France -- Genealogy -- Periodicals; Periodicals